The Political and Social Economy of Care in Nicaragua Familialism of Care under an Exclusionary Social Policy Regime - Voorend, Koen (2010)
Nicaragua is the second poorest country in the Western Hemisphere. Its gross domestic product (GDP) is extraordinarily low ($958 per capita), and its main source of income is the inflow of remittances from emigrant families working in the United States and Costa Rica. Seventy per cent of the population lives below the poverty line, and two out of 10 people are illiterate. Many households are headed by women, who are responsible for both care and paid work. Furthermore, Nicaragua is highly susceptible to natural (and social) disasters such as hurricanes and earthquakes. Within this complex reality, how do social practices in the household, state,community and markets combine and interact to provide care services and, in particular, care for children? Historically, the country has been a socialist state. Inadequate public investment in social protection and services resulted in limited coverage. Even under the import substitution model,and during the period when the state increased social protection, only a quarter of the population was covered. Currently, the welfare of the population depends to a large extent on family strategies designed to generate income and build social protection networks. Heavy dependence on emigration and remittances, self-employment through the transformation offamilies into productive units, and reliance on social networks to deal with illness and other unforeseen circumstances demonstrate the absence of clear boundaries between labour markets,social policy and the family. Over the last three decades, Nicaragua has undergone radical changes in its political and economic system. The early 1980s represented a honeymoon, following the Sandinista revolution. The second half of the decade was characterized by the embargo by the United States, counter-revolution, war and the introduction of structural adjustment programmes. The 1990s were marked by reconstruction, a transition to electoral democracy and economic liberalization. Through these three transitions, unpaid work by women, as well as volunteer work and community participation, played a central role in providing care services. During the 1980s, the Sandinista revolution significantly expanded education, health and care services, underpinned by a vision that social services should be provided by a strong centralized state serving the population as a whole. This expansion depended mostly on organizing and mobilizing volunteer workers. Moving away from this vision, the liberal governments of the 1990s promoted a subsidiary role for the state, with respect to both the market and households. Specifically, this meant the decentralization and targeting of services,as well as increased marketization of access through co-payment arrangements. These neoliberal changes also relied on large-scale efforts to mobilize unpaid women workers, recruit volunteers and encourage community participation. During the period studied in this paper—from the 1980s to the 2000s—the role of the state was, in various ways, subsidiary to that of unpaid, volunteer and community work, providing only rudimentary support. First, only the most basic social services were provided by the state (in the area of health services, for example, only primary care was offered), and coverage was far from adequate. Second, households and communities played a more dominant role than did public institutions. Third, most public programmes were dependent on strong family and community participation. Drawing on statistical sources, official documents and secondary sources, this paper explores the general features of the Nicaraguan social policy regime, in terms of both social spending and the principal components of education, health, social protection and actual care services. On the basis of 54 interviews with women and men from two very different municipalities— Managua and Estelí—the paper describes the prevailing care practices, interpreting them in the light of available time use statistics. Finally, it discusses the mix of public, market and family care practices in the context of the findings.